Benchmarking HR outsourcing literature: a critical literature review. (5th December 2022) - Sim, Siew-Chen; Mohan, Avvari V.; Kaliannan, Maniam; Vinayan, Gowrie; Harikirishanan, Davindran
This study synthesises more than 20 years of human resource outsourcing (HRO) empirical studies to answer research questions related to determinants of HRO decision. Using grounded coding technique adapted from Lacity et al. (2010), empirical papers published from 1997 to 2018 were coded. Two theoretical models emerged from the findings where the existence of definitional ambiguity, findings and competing theoretical perspectives which underlies HRO research were identified. This study offers insights from past HRO studies to help HRO researchers to better understand HRO phenomenon. It is acknowledged that coding technique neither generates statistical diagrams nor infographics, but it provides valuable insights for the overview of literature within the area of human resource outsourcing. Being the first HRO literature review that uses the grounded coded technique, this paper answers three research questions while laying important foundation for theory development.